Public awaraness of marine pollution in istanbul, Turkey - (:unkn) unknown (My University, 2010)
In this study, two districts of Istanbul, the most crowded city of Turkey,. were selected to determine the public consciousness on marine pollution by utilizing a specifically designed questionnaire consisting of 30 questions prepared by means of Geographical Information Systems (GIS). The questionnaire was randomly distributed at two districts in some preselected institutions and at various centers of these districts. The filled forms were graded and different queries as well as mappings were conducted and further displayed via GIS. For each district, utilizing the evaluations and the relationship between the public consciousnesses on marine pollution, age and education levels were displayed. The findings indicated that consciousness level and public awareness related to environmental issues like marine pollution increased parallel to education level. © by PSP.
Keywords: GIS; Istanbul; Marine pollution; Public consciousness; Questionnaire